Political outcomes of aid - Cruz, C; Labonne, J; Wright, A (Edward Elgar Publishing, 2024)
Development aid often has domestic political consequences - both intended and unintended. This chapter reviews the literature on the effect of aid on political outcomes in recipient countries. These consequences can result from mismatched priorities between aid agencies and recipients, the need to accommodate various actors within domestic governments at the national and local level, and strategic attempts on either side to manipulate aid projects for their benefit. We argue that those effects can arise due to salient features of foreign aid that lead to the introduction of new actors in domestic politics, the introduction of new incentives for leaders and an increase in available resources. Those can affect the strategic decisions of voters and local leaders with a range of potential consequences from institutional changes and strengthening state capacity to corruption, political capture and distortions.